Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fsurg.2021.779372
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Transperitoneal Para-Aortic Lymphadenectomy Compared With Extraperitoneal Approach in Gynecologic Cancers: A Systematic Review and Meta-Analysis

Abstract: Purpose: The optimal surgical approach for para-aortic lymphadenectomy (PALND) in gynecologic cancers using minimally invasive surgery (laparoscopy or robotic-assisted) is controversial. This study summarizes the current evidence on the extraperitoneal (EP) approach and compares its perioperative, surgical outcomes, and complications to the transperitoneal (TP) approach in an updated meta-analysis.Methods: We performed a systematic search in PubMed, Embase, Web of Science, Cochrane Library database for randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…Previous meta-analyses have reported that the ELPAN technique has certain advantages when compared with transperitoneal laparoscopic para-aortic lymphadenectomy (6,7). For example, the ELPAN technique makes it easier for the surgeon to approach the lymph nodes on the left side of the large vessels and can be easily applied in cases that involve intra-abdominal adhesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous meta-analyses have reported that the ELPAN technique has certain advantages when compared with transperitoneal laparoscopic para-aortic lymphadenectomy (6,7). For example, the ELPAN technique makes it easier for the surgeon to approach the lymph nodes on the left side of the large vessels and can be easily applied in cases that involve intra-abdominal adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analyses compared para-aortic lymphadenectomy using the extraperitoneal laparoscopic approach (ELPAN) with transperitoneal laparoscopic approaches in patients with endometrial cancer and reported that the ELPAN led to the successful harvesting of a higher number of para-aortic lymph nodes (6,7). In addition, the left-sided extraperitoneal technique was found to facilitate easy access to the left aortic nodes, which comprise 63% of all aortic nodes (8,9).…”
Section: Introductionmentioning
confidence: 99%